2004
DOI: 10.1128/jvi.78.23.13207-13215.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Replication-Incompetent Vector Derived from Adenovirus Type 11 (Ad11) for Vaccination and Gene Therapy: Low Seroprevalence and Non-Cross-Reactivity with Ad5

Abstract: A novel plasmid-based adenovirus vector system that enables manufacturing of replication-incompetent (⌬E1) adenovirus type 11 (Ad11)-based vectors is described. Ad11 vectors are produced on PER.C6/55K cells yielding high-titer vector batches after purification. Ad11 seroprevalence proves to be significantly lower than that of Ad5, and neutralizing antibody titers against Ad11 are low. Ad11 seroprevalence among human immunodeficiency virus-positive (HIV ؉ ) individuals is as low as that among HIV ؊ individuals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
123
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 41 publications
(57 reference statements)
5
123
0
Order By: Relevance
“…26,27 Furthermore, the incidence rate of seroconversion to many alternative serotype HAds in many cases are significantly lower than the seroconversion rates noted for HAd5. 28 These facts have justified multiple investigations into the use of alternative serotype Ads for potential use in numerous human gene transfer applications. 29 However, it is also likely that using alternative serotype Ads may also generate unanticipated biological consequences.…”
Section: Alternative Serotype Ads Exhibit Significantly Different Biomentioning
confidence: 99%
“…26,27 Furthermore, the incidence rate of seroconversion to many alternative serotype HAds in many cases are significantly lower than the seroconversion rates noted for HAd5. 28 These facts have justified multiple investigations into the use of alternative serotype Ads for potential use in numerous human gene transfer applications. 29 However, it is also likely that using alternative serotype Ads may also generate unanticipated biological consequences.…”
Section: Alternative Serotype Ads Exhibit Significantly Different Biomentioning
confidence: 99%
“…First, Ad11 and Ad35 are known to be rarely neutralized by human sera. 18 Second, Ad11 and Ad35 exhibit a broad tropism including cells expressing no or low levels of coxsackievirus and adenovirus receptor (CAR), which is a receptor for Ads belonging to subgroups A, C, D, E and F. 19 Several groups (including the authors) have developed replication-incompetent Ad vectors composed of subgroup B Ads [20][21][22][23][24] or fibersubstituted Ad serotype 5 (Ad5) vectors containing subgroup B Ad fibers, [25][26][27][28] and have demonstrated that these types of Ad vectors efficiently transduce a variety of human cells, including cells refractory to conventional Ad5 vectors. If surface CD46 downregulation occurs following transduction with CD46-utilizing Ad vectors, unexpected side effects might occur such as complementmediated cell lysis of successfully transduced cells, which leads to clearance of the transduced cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several important target cells for gene therapy, including hematopoietic stem cells, 7 dendritic cells (DCs) 8 and malignant tumor cells, 9 express low levels of CAR. To overcome these drawbacks of Ad5 vectors, several groups (including ours) have developed Ad vectors composed of other human Ad serotypes, such as Ad serotype 7a, 10 11 4,11 and 35, 12-15 and Ads of animal origin, such as chimpanzee, 16 bovine, 17 mouse 18 and ovine. 19 Among these non-Ad5 vectors, those composed of human Ad11 and Ad35, which belong to subgroup B, are highly promising as gene transfer vectors for the following reasons.…”
mentioning
confidence: 99%